Relationship between intellectual capital and financial performance: The moderating role of knowledge assets - Shahid Amin; Muhammad Usman; Nadeem Sohail; Shoaib Aslam (Pakistan Journal of Commerce and Social Sciences (PJCSS), 2018)
Beyond the recent studies on intellectual capital (IC), we investigate whether knowledge assets (KA) moderate the relationship between IC and firm performance (FP). We use the recent data of all Australian Stock Exchange (ASX) listed companies. To test the developed hypotheses, we use structural equation modeling (SEM) techniques. After ensuring the validity and reliability of measurement model, we find reliable evidence that KA strengthens the relationship between IC and FP, which suggest that the value of Australian listed firms can be synergized with IC and KA. In addition, our results show that IC and its components are positively associated with firms' financial performance. Similarly, KA is also positively associated with improved firm performance. This study contributes towards the literatures because this is the first study that explores the moderating role of KA in measuring the impact of intellectual capital on the firm's financial performance.
Keywords: 330; knowledge intensity; market knowledge; R&D intensity; human capital; structural capital